Preparation and Characterization of Nanoparticles TiO2 and Its Application for Methylene Blue Dye Degradation under Solar Light - Ahmed Hassan Ali (Journal of Global Pharma Technology, 2017)
This research paper study, the treatment of m ethylene blue dye was investigated in a photo catalyticsystem under solar irradiation in heterogeneous solution with multi concentrations like (0.3 , 0.8 , 1.3 ,and 2) g/l of commercial TiO2 as a photo catalyst. The optimum value of photo catalyst concentration (0.8mg/l) the nano particles TiO2 was prepared by using sol-gel technique. The properties of the preparedTiO2 were checked with X-ray and transmission electron microscopy technique. Then the treatment ofthe m ethylene blue dye was checked by using synthesis TiO2with same previous conditions. We havecompared the treatment efficiency of solution between the prepared nanoparticles and commercial TiO2.The results shows that the prepared TiO2hasa more efficiency. The practical work also includes therecycled ofTiO2 nano particles.Keywords: Photo catalytic Degradation; Titanium dioxide; Wastewater treatment; Preparation andcharacterization of nano particles.